RESIPROSITAS PENJUAL PEMBELI PADA APLIKASI TIKTOK - Anggi Vidia Nurjannah; Cicilia Larasati Rembulan; Jessica Noviana Onggono (EXPERIENTIA : Jurnal Psikologi Indonesia, 2022)
COVID-19 pandemic has led to changes in the way people shop online and has an impact on the emergence of a new phenomenon where the TikTok application becomes a medium for buying and selling online. With TikTok becoming online commerce medium, can cause practical-knowledge gap, by which negative behavior such as scams can happen during buying and selling activities occurs. With this phenomenon, the purpose of this research is to describe the pattern of buyer-seller reciprocity on TikTok social media. This research is included in qualitative research. Primary data used were obtained through informants and secondary data obtained through comments on the TikTok application. Participant characteristics were taken using purposive sampling technique and using a screening with an open questionnaire to find participants who would be interviewed. From the research results, it was found that the buyer-seller reciprocity pattern in TikTok contained three stages in the big theme. The first big theme is the predecessor condition, then it is continued at the process stage (interaction), and ends with output.